UPAYA PENINGKATAN HASIL BELAJAR DAN KEMAMPUAN MEMBACA INTENSIF PADA TEKS DESKRIPSI MELALUI STRATEGI DR-TA (Directed Reading Thinking Activity) PADA KELAS V SDN LOANO - Ayu Juliyani Permatasari; Arum Ratnaningsih; Suyoto (LPPM Universitas Cipta Mandiri, 2024)
Research has been conducted entitled Efforts to Improve Learning Outcomes and Intensive Reading Ability in Descriptive Texts Through the DR-TA (Directed Reading Thinking Activity) Strategy in Class V of SDN Loano which aims to 1) To determine the increase in learning outcomes through the DR-TA (Directed) learning strategy Reading Thinking Activity) in intensive learning in class V descriptive text material at Loano State Elementary School 2) To determine students' intensive reading abilities through the DR-TA (Directed Reading Thinking Activity) learning strategy in Indonesian language subjects in class V description text material at Loano State Elementary School 3) Describe the application of the DR-TA (Directed Reading Thinking Activity) learning strategy in the Indonesian language subject in descriptive text material for class V at Loano State Elementary School. This research design uses a type of classroom action research (PTK) with two cycles. The research subjects were class V students at SDN Loano. Data collection techniques used include interviews, observation, tests and documentation. IThe research results showed that learning outcomes in cycle I were obtained with a learning completeness percentage of 45.45% in the very low category, increasing in cycle II with a learning completeness percentage of 86.35% in the high category. The intensive reading ability of students in the first cycle obtained a percentage of 64.99% in the poor category, increasing in the second meeting, the percentage obtained was 86.13% in the good category. The implementation of learning in cycle I obtained a percentage of 75% in the medium category, increasing in cycle II, the percentage obtained was 90% in the very good category. Thus, the application of the DR-TA (Directed Reading Thinking Activity) Strategy can improve learning outcomes and students' intensive reading abilities in class V descriptive text material at SDN Loano.